Comparative Moisture Management Studies of Single Jersey Knitted Soya Bean Fabrics. Issue 16 (28th November 2022) - Margret Soundri, Geetha; S, Kavitha; Boominathan, Senthilkumar; Raj, D. Vijay; Patchiyappan, K. M.
ABSTRACT: In recent times, due to increased environmental awareness, the usage of sustainable, eco-friendly textile products has gained momentum. In this respect, the Soya bean protein fiber (SPF) based fabric structure is considered a potential product. Single Jersey and Single Pique knitted structures were developed by changing the yarn count and loop length using Soya bean fiber for next-to-skin applications. Multidimensional moisture management properties were measured using MTT tester to understand the influence of process parameters (fabric structure yarn count and loop length). Further to this, physical properties and wetness comfort properties of the SPF knitted fabrics were also studied. It was found that the OMMC properties of most of the SPF knitted samples were highly rated. The influence of knit structure, yarn count, and loop length on moisture properties was studied through ANOVA. Similarly, the correlation between the physical parameters and moisture properties was also investigated. The Single Pique structure with finer yarn count and higher loop length configuration showed higher moisture management properties. The fabric thickness was correlated with all the moisture management properties. However, the fabric tightness factor was correlated with all the moisture management properties except MWR and AOTI.